A spatiotemporal analysis of dengue hemorrhagic fever in Banyumas, Indonesia - Dwi Sarwani Sri Rejeki; Nunung Nurhayati; Budi Aji (Intelektual Pustaka Media Utama, 2021)
Dengue hemorrhagic fever (DHF) is a public health problem in the world and also in Indonesia. One of the districts in Central Java that is still having problems with this disease is Banyumas, Indonesia. The incidence rate (IR) data in 2018 was 2.75 per 100,000 populations and the case fatality rate (CFR) was 3.64%. Spatiotemporal analysis was used to determine local variation, geographic determination of risk zones, and measurement of disease control interventions. Therefore, this study aimed to determine the distribution and grouping of dengue cases based on the spatiotemporal analysis. The design was observational with a cross-sectional spatial analysis. This study was conducted in Banyumas, Indonesia with the analysis unit for dengue fever patients in 2018 using as many as 57 cases. Furthermore, the data analysis used includes overlay, buffering, and clustering with SaTScan and ArcGis software. The results showed that there was a clustering of dengue cases in Banyumas, with one primary and three secondary clusters detected. The primary cluster occurred in March-April 2018, involving four sub-districts in urban areas. It was then concluded that the significantly identified clusters indicate a transmission of dengue fever in the Banyumas area with a radius of three kilometers.